PENERAPAN METODE MIND MAPPING UNTUK MENINGKATKAN KEMAMPUAN MENGINGAT SISWA PADA PEMBELAJARAN IPA TENTANG STRUKTUR TUMBUHAN DI KELAS IV SD NEGERI KARANGLAYUNG - Siti Sahronih; Mochamad Guntur; Risma Nurlatifah (Institut Pendidikan dan Bahasa Invada, 2021)
Technology-based learning currently requires its implementation to utilize the latest innovations for the renewal of the teaching and learning process in it. The use of e-learning is one option that can be done with the current online learning. This study aims to determine the application of learning using e-learning by going through five stages of development with reference to the development of the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results of this study are the development of e-learning at SMKN 1 Majalengka using the ADDIE development model, namely analysis, design, development, implementation, and evaluation; (b) the resulting e-learning has an online class feature that can be used to assist practical learning as well as distance learning. This online class can be used as a face-to-face online medium when the teacher cannot be present in class; (c) assessment of the feasibility of e-learning learning media; (d) e-learning gets an average assessment from media experts, so that e-learning learning media is categorized with the